Bank exposures and sovereign stress transmission - Carlo Altavilla; Marco Pagano; Saverio Simonelli (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
Using novel monthly data for 226 euro-area banks from 2007 to 2015, we investigate the causes and effects of banks' sovereign exposures during and after the euro crisis. First, in the vulnerable countries, the publicly owned, recently bailed out and less strongly capitalized banks reacted to sovereign stress by increasing their domestic sovereign holdings more than other banks, suggesting that their choices were affected both by moral suasion and by yield-seeking. Second, their exposures significantly amplified the transmission of risk from the sovereign and its impact on lending. This amplification of the impact on lending cannot be ascribed to spurious correlation or reverse causality.
Keywords: E44; F3; G01; G21; H63; 330; sovereign exposures; sovereign risk; credit risk; diabolic loop; lending; euro debt crisis